2018
DOI: 10.11118/actaun201866041073
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Older Workers on the Labour Market

Abstract: This article focuses on position of older workers on labour market. It tries to identify and shortly describe the main factors affecting chances of older workers to get and keep a job. There are many approaches how to evaluate the opportunities and obstacles faced by older workers. On the basis of review of literature this paper points to significant problems that population ageing can bring to labour market. The differences between changes in productivity and changes in earnings might lead to reduction of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, at higher educational level, older workers were significantly more likely to boost productivity of a firm rather than younger workers. In addition to the factor of working conditions, there is no exact inclination for whether part-time or full-time working is suitable for older workers [ 22 , 37 , 38 , 39 ]. Göbel and Zwick [ 22 ] showed that working part-time would provide positively significant effects on the productivity of workers in the service sector, lower effects in manufacturing industries, and no significant effect on the metalworking sector.…”
Section: Relevant Studies: Defining Productivity and Its Determinantsmentioning
confidence: 99%
“…However, at higher educational level, older workers were significantly more likely to boost productivity of a firm rather than younger workers. In addition to the factor of working conditions, there is no exact inclination for whether part-time or full-time working is suitable for older workers [ 22 , 37 , 38 , 39 ]. Göbel and Zwick [ 22 ] showed that working part-time would provide positively significant effects on the productivity of workers in the service sector, lower effects in manufacturing industries, and no significant effect on the metalworking sector.…”
Section: Relevant Studies: Defining Productivity and Its Determinantsmentioning
confidence: 99%